Exploring the benefits of in-diet versus repeated oral dosing of saracatinib (AZD0530) in chronic studies: insights into pharmacokinetics and animal welfare - Vasanthi, Suraj S.; Massey, Nyzil; Nair, Suresh N.; Mochel, Jonathan P.; Showman, Lucas; Thippeswamy, Thimmasettappa (Frontiers in Veterinary Science, 2023)
Saracatinib/AZD0530 (SAR), a Src tyrosine kinase inhibitor, mitigates seizure-induced brain pathology in epilepsy models upon repeated oral dosing. However, repeated dosing is stressful and can be challenging in some seizing animals. To overcome this issue, we have incorporated SAR-in-Diet and compared serum pharmacokinetics (PK) and brain concentrations with conventional repeated oral dosing. Saracatinib in solution or in-diet was stable at room temperature for >4 weeks (97±1.56%). Adult Sprague Dawley rats on SAR-in-Diet consumed ~1.7g/day less compared to regular diet (16.82±0.6 vs. 18.50±0.5g/day), but the weight gain/day was unaffected (2.63±0.5g/day vs. 2.83±0.2g/day). Importantly, we achieved the anticipated SAR dose range from 2.5-18.7mg/kg of rat in response to varying concentrations of SAR-in-Diet from 54 to 260 ppm of feed, respectively. There was a strong and significant correlation between SAR-in-Diet dose (mg/kg) and serum saracatinib concentrations (ng/ml). Serum concentrations also did not vary significantly between SAR-in-Diet and repeated oral dosing. The hippocampal saracatinib concentrations derived from SAR-in-Diet treatment were higher than those derived after repeated oral dosing (day 4, 546.8±219.7ng/g vs. 238.6±143ng/g; day 7, 300.7±43.4ng/g vs. 271.1±62.33ng/g). Saracatinib stability at room temperature and high serum and hippocampal concentrations in animals fed on SAR-in-Diet are useful to titer the saracatinib dose for future animal disease models. Overall, test drugs in the diet is an experimental approach that addresses issues related to handling stress-induced variables in animal experiments.